SELF-ORGANIZING MAPS WITH SLIDING WINDOW (SOM plus SW) - Celenk, Ulas; Ertugrul, Duygu Celik; Zontul, Metin; Ucan, Osman Nuri (Univ Osijek, Tech Fac, 2017)
SOM is a popular artificial neural network algorithm to perform rational clustering on many different data sets. There is a disadvantage of the SOM that can run on a predefined completed data set. Various problems are encountered on a time-stream data sets when clustering by using standard SOM since the time-stream data sets are generated dependent on time. In this study, the Sliding Window feature is included into standard SOM for clustering time-stream data sets. Thus, the combination of SOM and Sliding Window (SOM + SW) gives more accurate results when clustering on time-stream data sets. To prove this, a set of internet usage data from a mobile operator in Turkey is taken to test. The taken data set from the mobile operator is clustered according to the classical SOM then the future data usages of subscribers are estimated. The same data set is applied on the SOM + SW to perform the same simulations.
Keywords: clustering; mobile operators; self-organizing maps (SOM); sliding window; time-stream data sets